Platforms of the Andalusian Government’s Education Authority and the educational inspection plan - Martínez-Serrano, María del Carmen (Avances en Supervisión Educativa, 2019)
The following article revises the main educational platforms implemented in the schools and services which depend on the Andalusian Government’s Education Authority (Consejería de Educación de la Junta de Andalucía), defining for each one of them, their characteristics, the main objectives fulfilled by its creation or implementation, the agents which is addressed to, etc. Additionally, it examines the framework for the Andalusian Inspection Programme and how the aforementioned platforms fit inside its programmed actions as helping resources for school management, acquisition tools for information about the schools’ actuality, in addition to their role as aids in the supervision, assessment and control of de educative system, an essential function of the education inspection. Finally, conclusions are drawn and implications gathered as to this respect.
Keywords: educational Inspection; educational platforms; educational supervision; networking; collaborative working; ICT